Isomorphism Theorems on Intuitionistic Fuzzy Abstract Algebras - í‡uvalcıoğlu, Gökhan; Tarsuslu (Yılmaz), Sinem (Communications in Mathematics and Applications, 2021)
The concept of abstract algebra on intuitionistic fuzzy sets were introduced and some basic theorems were proved by authors in 2017. In this study, homomorphism between intuitionistic fuzzy abstract algebras is defined, intuitionistic fuzzy function is examined and then intuitionistic fuzzy congruence relations are defined on intuitionistic fuzzy abstract algebra. First and third isomorphism theorems on intuitionistic abstract algebras are introduced.